Azerbaycan’da bağımsızlığa adanmış bir ömür: Fethali han hoyski (1875-1920) - AKARSLAN, ZEYNEP (My University, 2024)
1828 yılında imzalanan Türkmençay Antlaşması ile toprakları kuzey ve güney olmak üzere ikiye ayrılan Azerbaycan, bu tarihten 1918 yılına kadar Çarlık Rusya egemenliği altında varlığını sürdürdü. Çarlık Rusya’da 1917 yılında meydana gelen Bolşevik İhtilali uzun yıllardır Rusya egemenliği altında yaşayan milletlerin bağımsızlığı için umut ışığı oldu. Bu dönemde Azerbaycan’ın bağımsızlığı için mücadele eden isimlerden biri de Fethali Han Hoyski’dir. Cafer Kulu Han neslinden gelen Fethali Han Hoyski, eğitimini Moskova’da aldıktan sonra 2. Rus Devlet Duması’nda Azerbaycan’ı temsil etmiş, daha sonra Transkafkasya Seymi’nde önce eğitim işleri ile ilgilenmiş ardından Adalet Bakanı olarak görev yapmıştır. Bir avukat olarak siyasi kariyerine başladığı ilk günden itibaren hak eşitliği, özgürlük ve adalet kavramlarının savunucusu olan Fethali Han, Azerbaycan Cumhuriyeti’nin 1918-1920 yılları arasındaki kısa bağımsızlık döneminin ilk Başbakanı, Dışişleri Bakanı, İçişleri Bakanı ve Adalet Bakanıdır. Bu çalışma, Fethali Han Hoyski’nin nesli ve Azerbaycan siyasi tarihindeki yeri ve öneminin anlaşılması açısından arşiv belgeleri ve dönemin kaynakları ışığında oluşturulmuştur. Anahtar Kelimeler: Fethali Han Hoyski, Azerbaycan, Kafkasya, bağımsızlık, Bolşevik Rusya.

Azerbaijan, whose lands were divided into two as north and south with the Treaty of Turkmenchay signed in 1828, continued its existence under the rule of Tsarist Russia from this date until 1918. The Bolshevik revolution that took place in Tsarist Russia in 1917 was a beacon of hope for the independence of the nations that had been under Russian rule for many years. In this period, one of the names who struggled for the independence of Azerbaijan was Fethali Khan Khoyski. Fethali Han Hoyski, who is from the generation of Cafer Kulu Khan, received his education in Moscow and went to II. He represented Azerbaijan in the Russian State Duma, then in the Transcaucasian Seym he first dealt with educational affairs and then served as the Minister of Justice. Fethali Khan, who has been a defender of the concepts of equality of rights, freedom and justice since the first day he started his political career as a lawyer, is the first Prime Minister, Minister of Foreign Affairs, Minister of Internal Affairs and Minister of Justice of the Republic of Azerbaijan in the short independence period between 1918-1920. This study has been discussed in the light of archival documents and sources of the period in order to understand the place and importance of Fethali Khan Khoyski in the political history of Azerbaijan. Keywords: Fethali Khan Hoyski, Azerbaijan, Caucasia, independence, Bolshevik Russia.
A Life Dedicated to Independence in Azerbaijan: Fethali Khan Hoyski (1875-1920)
Keywords: Fethali Han Hoyski; Azerbaycan; Kafkasya; bağımsızlık; Bolşevik Rusya; Fethali Khan Hoyski; Azerbaijan; Caucasia; independence; Bolshevik Russia